CHALLENGES AND RECENT DEVELOPMENTS ASSOCIATED WITH VACCINE ANTIGENS PRODUCTION AGAINST HELICOBACTER PYLORI - BARZIGAR, RAMBOD; HARAPRASAD, NANJUNDAPPA; KUMAR, BASARALU YADURAPPA SATHISH; MEHRAN, MOHAMMAD JAVAD (International Journal of Applied Pharmaceutics, 2020)
Around half of the world’s population faces Helicobactor pylori (H. pylori) infection. Enormous progress has been made to understand the bacterial pathogenesis process and pathogen interaction with eukaryotic cells but infectious diseases are still the cause of premature death of humans around the world. H. pylori is categorized under class I carcinogen by the WHO based on clinical study results. This review paper discusses various attempts made to establish an efficient vaccine to manage H. pylori infection. Some of the problems in developing an efficient vaccine against H. pylori are recurrent or persistent infection, insufficient knowledge about the action specifically in case of probiotics, development of antibiotic resistance, and cost of therapy are noted. This research may come up with transient Nicotiana benthamiana with suitable H. pylori genes expressed as antigenic proteins, which can be used for further studies to develop a vaccine for gastric ulcer/cancer and generate good scientific data that can be helpful for scientists and researchers in this field. This review article for monitors’ current approaches monitoring H. pylori infection since 1998 to 2019 using world-wide recognized journals and books, questioning its efficacies and whether these strategies help eradicate or there is a need to focus on several diversions. We provide scientific recommendations in eliminating H. pylori through vaccination along with addressing the preventive vaccine for this pathogen rather than using defeated treatments with plant-based nil side effects solution. The information relies on the available content in Google Scholar and PubMed using the keywords listed below.